2010
DOI: 10.1186/1465-9921-11-114
|View full text |Cite
|
Sign up to set email alerts
|

The presence of serum anti-Ascaris lumbricoides IgE antibodies and of Trichuris trichiura infection are risk factors for wheezing and/or atopy in preschool-aged Brazilian children

Abstract: BackgroundThe elucidation of factors that trigger the development of transient wheezing in early childhood may be an important step toward understanding the pathogenesis of asthma and other allergic diseases later in life. Transient wheezing has been mainly attributed to viral infections, although sensitisation to aeroallergens and food allergens may occur at an early age. In developing countries, intestinal helminthic infections have also been associated with allergy or atopy-related disorders.ObjectiveThe ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 24 publications
1
53
1
Order By: Relevance
“…It may also be deduced that those with trichuriasis may indeed, possibly mediate allergy especially with aeroallergens as exhibited by its highest total IgE level among the three types of parasitic infections. This is parallel with the sutdy of Cooper (2004) and Alcântara-Neves et al (2010) which proposed the idea that Trichuris trichiura infection may mediate allergy with inhalants. The data corroborate with prior investigations showing considerable increased serum IgE levels with children irrespective of age (Arbes et al, 2011) and type of allergy (Erwin et al, 2010;Levin, Le Souëf, & Motala, 2008).…”
Section: ≥10 Years Old (N=11)mentioning
confidence: 63%
See 2 more Smart Citations
“…It may also be deduced that those with trichuriasis may indeed, possibly mediate allergy especially with aeroallergens as exhibited by its highest total IgE level among the three types of parasitic infections. This is parallel with the sutdy of Cooper (2004) and Alcântara-Neves et al (2010) which proposed the idea that Trichuris trichiura infection may mediate allergy with inhalants. The data corroborate with prior investigations showing considerable increased serum IgE levels with children irrespective of age (Arbes et al, 2011) and type of allergy (Erwin et al, 2010;Levin, Le Souëf, & Motala, 2008).…”
Section: ≥10 Years Old (N=11)mentioning
confidence: 63%
“…It clearly indicates that many of the children with geohelminthiasis were more prone to be allergic to inhalants than seafood. According to Barreto et al (2006), Fallon and Mangan (2007) and Lee et al (2013), this may suggest that intestinal parasitic infection may play a role in the development of atopy notably, respiratory allergies Alcântara-Neves et al, 2010;Cauyan et al, 2012;Beyers et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next link was the finding that both, helminthiases and allergy, were associated with high levels of total IgE, which was further extended to other features of the immune responses to both processes [65][66][67][68]. This has been followed by epidemiological reports that, using several approaches, have shown that ascariasis is a risk factor for asthma [69][70][71][72][73][74][75][76][77]. However, although there is abundant scientific literature supporting the boosting effect of ascariasis on allergic responses [5, 63- (Table 2), a number of questions remain regarding the mechanisms for inducing an increased allergic response and asthma symptoms in a condition naturally accompanied by immunosuppression (reviewed in [99,100]).…”
Section: The Complex Relationship Between Ascariasis and Allergymentioning
confidence: 99%
“…Natural infection is associated with a polarized Th2 cytokine response and high levels of total and anti-Ascaris IgE [5,65,73,[78][79][80][81][82][83][84][85] In some individuals, natural infection induces IgE-mediated allergic respiratory and cutaneous symptoms [63,86,87] In experimental human and animal models, bronchial challenges with Ascaris extract induce asthma symptoms [64,66,67] Experimental ascariasis in animals enhances IgE response to bystander antigens [88][89][90][91] Human ascariasis enhances IgE response to mite species-specific allergens [92, 93•, 94•] Several epidemiological surveys have found that ascariasis is a risk factor for asthma and atopy [69-75, 93•, 94•, 95, 96•] IgE responses to Ascaris allergens is more frequent and stronger in mite-sensitized asthmatic patients [76,81,97,98] could also increase symptoms and severity of this disease. Ascaris components and host genetic background influencing this boosting effect are only beginning to be unraveled, and deserve further investigations.…”
Section: Finding Referencesmentioning
confidence: 99%